2023
DOI: 10.3390/nano13040772
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Composite Methacrylated Gellan Gum for 3D-Printed Bone Tissue-Engineered Scaffolds

Abstract: Gellan gum (GG) was chemically modified with methacrylic moieties to produce a photocrosslinkable biomaterial ink, hereinafter called methacrylated GG (GGMA), with improved physico-chemical properties, mechanical behavior and stability under physiological conditions. Afterwards, GGMA was functionalized by incorporating two different bioactive compounds, a naturally derived eumelanin extracted from the black soldier fly (BSF-Eumel), or hydroxyapatite nanoparticles (HAp), synthesized by the sol–gel method. Diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Jo et al demonstrated that the injection of chitosan-PEO hydrogel, in combination with BMP-2 and MSCs, promoted bone formation in vivo [83]. Despite their limitations in terms of biocompatibility and biodegradability in vivo [84], their flexibility, i.e., the ability to adjust the structural parameters during the manufacturing processes [85], and the possibility of minimally invasive implantation [86], strongly encourage their application in the BTE field.…”
Section: Biomaterials For Bte Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jo et al demonstrated that the injection of chitosan-PEO hydrogel, in combination with BMP-2 and MSCs, promoted bone formation in vivo [83]. Despite their limitations in terms of biocompatibility and biodegradability in vivo [84], their flexibility, i.e., the ability to adjust the structural parameters during the manufacturing processes [85], and the possibility of minimally invasive implantation [86], strongly encourage their application in the BTE field.…”
Section: Biomaterials For Bte Applicationsmentioning
confidence: 99%
“…Specifically, HA NPs are generally combined with synthetic polymers like PLA [214,215] and PCL [216,217] in order to overcome their limits for clinical uses by enhancing cell adhesion and mineral deposition in vitro. For the same reason, HA NPs were also used to improve the mechanical and biological properties, as well as the stability under physiological conditions, of hydrogel scaffolds, such as Gellan Gum, in which it was observed that the integration of HA NPs enhanced cell proliferation and ALP activity in vitro [84].…”
Section: Ceramic Npsmentioning
confidence: 99%
“…Alvel et al [52] also prepared a composite hydrogel of xanthan with Konjac glucomannan, which also focused on wound healing. On the other hand, a 3D scaffold for tissue engineering was prepared with alginate-gellan gum [53] and methacrylated gellan gum [54]. The applications of EPS composites with various polymers have been summarized below:…”
Section: Exopolysaccharide Composites With Natural Materialsmentioning
confidence: 99%